Effect of Post-Infiltration Soil Aeration at Different Growth Stages on Growth and Fruit Quality of Drip-Irrigated Potted Tomato Plants (Solanum lycopersicum) - Li, Yuan (PLoS One, 2015)
Soil hydraulic principles suggest that post-infiltration hypoxic conditions would be induced in the plant root-zone for drip-irrigated tomato production in small pots filled with natural soil. No previous study specifically examined the response of tomato plants (Solanum lycopersicum) at different growth stages to low soil aeration under these conditions. A 2 × 6 factorial experiment was conducted to quantify effects of no post-infiltration soil aeration versus aeration during 5 different periods (namely 27–33, 34–57, 58–85, 86–99, and 27–99 days after sowing), on growth and fruit quality of potted single tomato plants that were sub-surface trickle-irrigated every 2 days at 2 levels. Soil was aerated by injecting 2.5 liters of air into each pot through the drip tubing immediately after irrigation. Results showed that post-infiltration aeration, especially during the fruit setting (34–57 DAS) and enlargement (58–85 DAS) growth stages, can positively influence the yield, root dry weight and activity, and the nutritional (soluble solids and vitamin C content), taste (titratable acidity), and market quality (shape and firmness) of the tomato fruits. Interactions between irrigation level and post-infiltration aeration on some of these fruit quality parameters indicated a need for further study on the dynamic interplay of air and water in the root zone of the plants under the conditions of this experiment.